Pengembangan Buku Zingiberaceae sebagai Eksplorasi Kearifan Lokal Sabang - Saudah Saudah; Deta Pristihayati; Adi Hartono; Dian Aswita (Biosfer: Jurnal Pendidikan Biologi, 2026)
The integration of local wisdom into biology learning resources remains limited, particularly in transforming ethnobotanical knowledge into scientifically validated instructional materials. This study aimed to develop a Zingiberaceae book based on Sabang’s local wisdom as a contextual biology learning resource. The research employed the 4D development model (Define, Design, Develop, Disseminate), but was limited to the Develop stage through expert validation. In the Define stage, curriculum needs, learner characteristics, and local biological potential were analyzed. The Design stage produced a prototype integrating scientific concepts of Zingiberaceae—such as taxonomy, morphology, phytochemistry, and ecological roles—with ethnobotanical information and cultural practices of the Sabang community. In the Develop stage, the product was evaluated by material experts, language experts, and teaching material experts using structured validation instruments. The results showed that material expert validation reached 92%, language expert validation reached 88%, and teaching material expert validation reached 90%, all categorized as very valid. The overall average validity score was 90%, indicating that the book fulfills the criteria of scientific accuracy, linguistic clarity, and instructional feasibility. The findings demonstrate that ethnobotanical knowledge can be systematically transformed into a valid contextual biology learning resource. Therefore, the developed book is recommended as an enrichment material to support contextual learning and strengthen the integration of local wisdom in biology education.